Key roles of autophagy in the regulation of T-cell function - Botbol, Yair (Eur J Immunol, 2016)
In the past 10 years, autophagy has emerged as a crucial regulator of T-cell homeostasis, activation and differentiation. Through the ability to adjust the cell’s proteome in response to different stimuli, different forms of autophagy have been shown to control T-cell homeostasis and survival. Autophagic processes can also determine the magnitude of the T-cell response to TCR engagement, by regulating the cellular levels of specific signaling intermediates and modulating the metabolic output in activated T-cells. In this review we will examine the mechanisms that control autophagy activity in T-cells, such as ROS signaling and signaling through common gamma-chain cytokine receptors, and the different aspect of T-cell biology, including, T-cell survival, effector cell function and generation of memory, which can be regulated by autophagy.